PELAKSANAAN KEADILAN RESTORATIF DALAM PENYELESAIAN TINDAK PIDANA RINGAN DI RUMAH RESTORATIF DI NAGARI SALIMPEK KABUPATEN SOLOK - Firdaus Firdaus; Besse Patmawanti (Ensiklopedia of Journal, 2023)
Abstract: The implementation of non-litigation settlement of criminal acts as stated in article 4 of the Attorney General's Regulation of the Republic of Indonesia Number 15 of 2020 concerning termination of prosecution based on restorative justice is the basis for efforts to fulfill the rights of perpetrators and victims. However, the implementation of restorative justice in the settlement of minor crimes still finds pros and cons in the community, so this certainly cannot immediately conclude whether restorative justice policies are not good at fulfilling the rights of perpetrators and victims. Nevertheless, in Nagari Salimpek, Solok Regency, criminal acts have been resolved through restorative justice. This research is a descriptive research, namely research conducted by describing and describing the object of research or the problem under study related to the implementation of restorative justice in the restorative house of Nagari Salimpek, Solok Regency. The approach methods used include the main approach in a normative juridical manner, namely the legal research method carried out by examining library materials or secondary data and supported by an empirical juridical approach, namely the research method carried out to obtain primary data. From the results of research and discussion, it can be drawn the conclusions are as follows: First, the implementation of restorative justice in the settlement of minor crimes at the restorative home of Nagari Salimpek, Solok Regency is an alternative settlement of minor criminal cases that focuses on dialogue and mediation processes involving perpetrators, victims, families of perpetrators/victims, and other related parties to jointly create an agreement on a fair and balanced settlement of criminal cases for both victims and perpetrators by prioritizing restoration to their original state and restoring the pattern of good relations in society or commonly known as a win win solution. The Batanding Salah tradition is customary law used for the settlement of minor crimes in a non-litigation manner which aims to create a better society and village. Second, the obstacles in implementing the settlement of minor crimes based on restorative justice in the Nagari Salimpek restorative house, namely the lack of public understanding of restorative justice, the application of fines varies in number because there are no rules regarding the benchmark for the amount of fines for minor crimes that occur , as well as the lack of efficiency in the use of fines handed over to the perpetrators to the victims and to the local government.Keywords: Restorative Justice, Misdemeanors, Nagari Salimpek.